2003
DOI: 10.1002/cem.828
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of rank reduction problems with Wedderburn's formula

Abstract: In first-and second-order calibration methods based on spectroscopic data, the calculation of the space spanned by the spectra of the interferences has been an important research subject for, among many other applications, calculating the net analyte signal and obtaining figures of merit. Recently, many different calculation methods have been introduced. We show that the calculation of this space can be interpreted from a unified point of view, namely from the rank-one downdating Wedderburn formula. This formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The net analyte signal was defined as the part of the signal that is orthogonally to the space spanned by the spectra of the other components. Ferre 23,24 presents an improved calculation method for the NAS in inverse models propose by Lorber for the common equations of principal component regression (PCR) and partial least squares (PLS) regression. In the same time, another NAS‐based algorithm was presented by Berger et al 25 called hybrid linear analysis (HLA), which was recommended where the spectrum of the desired species was available.…”
Section: Introductionmentioning
confidence: 99%
“…The net analyte signal was defined as the part of the signal that is orthogonally to the space spanned by the spectra of the other components. Ferre 23,24 presents an improved calculation method for the NAS in inverse models propose by Lorber for the common equations of principal component regression (PCR) and partial least squares (PLS) regression. In the same time, another NAS‐based algorithm was presented by Berger et al 25 called hybrid linear analysis (HLA), which was recommended where the spectrum of the desired species was available.…”
Section: Introductionmentioning
confidence: 99%
“…Lorber 4 showed that the solution can be found in noniterative fashion by expressing the reduction in rank as a generalized eigenvalue problem. 45 5 RAFA was found to give reasonable estimates when the concentration of the analyte is large, but overestimated predictions when the signal of the analyte was very small compared to the background.…”
Section: Rank Annihilation Factor Analysismentioning
confidence: 91%
“…The net analyte signal was defined as the part of the signal that is orthogonally to the space spanned by the spectra of the other components. Ferré [4][5][6] presents an improved calculation method for the NAS in inverse models propose by Lorber for the common equations of principal component regression (PCR) and partial least squares (PLS) regression. In the same time, another NAS-based algorithm was presented by Berger et al [7] called hybrid linear analysis (HLA), which was recommended where the spectrum of the desired species was available.…”
Section: Introductionmentioning
confidence: 99%